2020
DOI: 10.5694/mja2.50817
|View full text |Cite
|
Sign up to set email alerts
|

COVID ‐19 in a Sydney nursing home: a case study and lessons learnt

Abstract: Perspectives COVID-19 in a Sydney nursing home: a case study and lessons learnt Lessons learnt from COVID-19 outbreaks in residential aged care facilities could limit future impacts I nfectious disease outbreaks are a hazard of communal living in places such as military barracks, boarding schools, prisons and residential care homes. The risks are exacerbated when residents are vulnerable because of advanced age, comorbidities and frailty, or there are too few or inadequately trained staff. The home-like settin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 16 publications
1
37
0
3
Order By: Relevance
“…The studies were all observational in nature. [ [11] , [12] , [13] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] ] All of the studies reported RT-PCR-confirmed COVID-19 cases amongst the residents.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The studies were all observational in nature. [ [11] , [12] , [13] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] ] All of the studies reported RT-PCR-confirmed COVID-19 cases amongst the residents.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…However, empirical evidence of whether learning and practice change occurs is scarce, especially in times of crisis. Lessons learned from a RACF outbreak in Sydney were that additional training by infection prevention and control professionals improved compliance with infection control and contributed to controlling the outbreak 11 . As of early August 2020, the Victorian government is offering free face‐to‐face infection control for all Victorian RACFs without outbreaks.…”
Section: Training Of Staffmentioning
confidence: 99%
“…The MJA has engaged in the debate about how to protect health care workers from infection, 10 a devastating outcome of the pandemic that was largely preventable. MJA authors have jumped into the often heated debates about schools and virus transmission, 11 the value of face masks, 12 the positive and negative effects of various public health measures, 10,13 lessons learned in an early nursing home outbreak, 14 the urgency of ensuring sufficient numbers of intensive care beds, 15 professional guidelines, 16,17 and protecting Indigenous Australians, 18 to name a few of the areas touched upon in our Journal. As, despite evidence and expert agreement, aberrant beliefs continued to circulate widely on social media, often causing alarm, the MJA has provided a source of reputable peer‐reviewed evidence, with expert syntheses of what is known and what has changed, published as rapidly as is responsible 19…”
Section: Our Response To the Covid‐19 Pandemicmentioning
confidence: 99%